An 80-Year-Old Female with Benign Paroxysmal Positional Vertigo and Isolated Systolic Hypertension with a Risk Factor of Eldery - Siswati, Bella; Dasa Novita, Khuznita; Dwi Rahayu, Indriati (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2024)
Benign Paroxysmal Positional Vertigo (BPPV) and isolated systolic hypertension are common conditions in the elderly population. This article discusses the case of an 80-year-old female with a combination of these conditions, where advanced age serves as a significant risk factor. A multidisciplinary approach was employed, involving therapy for BPPV management and tailored lifestyle modifications and pharmacological therapy for systolic hypertension. The study highlights the importance of comprehensive assessment of age-related risk factors, integrated symptom management, and the family’s role in supporting patient care. The findings suggest that individualized and collaborative care strategies can improve the quality of life in elderly patients.